Strategi pembelajaran yang komunikatif berbasis media siniar - Teti Setiawati; Musyarrafah Sulaiman Kurdi; Muqarramah Sulaiman Kurdi; Anda Prasetyo Ery; Matius Tinna Sarira (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2022)
Schools use online student learning techniques in an effort to stop the Covid-19 pandemic. This government initiative aims to break the chain of the spread of Covid-19. Due to the lack of mastery of technology, many teachers in schools are still confused about how to use the online learning system and only give assignments without explaining the contents. As a result, online learning loses its effectiveness, which has an impact on student learning outcomes. This study aims to determine the Podcast media-based learning strategy. The method used in this study is a literature review. The unit of analysis in this study is journal articles that have been collected by researchers through Google Scholar during the period of 2022. The conclusion of this study shows that the learning strategy using Podcast media must involve consideration and introduction from the teacher first. Teachers need to know the age and level of education of students. In addition, to understand the material presented is theoretical or practical.